Action for smart healthy age-friendly environments - van Staalduinen, Willeke (Magyar Gerontológia, 2021)
Smart, adaptable and inclusive solutions can help improve and support independent life throughout the course of life, regardless of age, gender, disabilities, cultural differences and personal choices.A holistic approach that optimizes social and physical environments, supported by digital tools and services, allows to provide better health and social care, promoting not only independent living, but also equity and active participation in society. This approach follows the United Nations' line-up, with the Sustainable Development Goals (in particular Objectives 3 and 11), stating that sustainable environments for all ages represent the basis for ensuring a better future for the entire population.The challenges of different sectors, such as ICT, the building industry and urban planning and the health and social care, as well as those of citizens and their communities are interlinked. Responding to these challenges will foster awareness and support for the creation and implementation of smart, healthy and inclusive environments for present and future generations.From this insight, a new concept was developed and well received: Smart Healthy Age-Friendly Environments (SHAFE). The by the EC approved Thematic Network of 2018 evolved into a Stakeholders Network of about 170 organisations and it is represented in several European projects and networks. COST Action NET4Age-Friendly brings together over 320 researchers from 46 countries. Capacity building to support the implementation of SHAFE is present in Erasmus+ projects.The presentation will give an overview of relevant development and insights to support the building of smart, inclusive societies.